42. THE SATISFACTION OF INPATIENTS WITH THE USE OF MEDICAL SERVICES AT TAM DAO DISTRICT MEDICAL CENTER, VINH PHUC PROVINCE, IN 2024. (Vietnam Journal of Community Medicine, 2025)
Objectives: Assessment of inpatients' satisfaction with medical services in clinical departments at Tam Dao District Medical Center in 2024.Method: Cross-sectional descriptive study.Results: The study, conducted on 218 participants at Tam Dao Medical Center, revealed an average age of 55.27 ± 15.72 years. Most participants lived in rural areas and used health insurance. The overall patient satisfaction rate with Tam Dao Medical Center was 89.4%. The highest satisfaction was related to the attitude and professionalism of medical staff (98.6%), while the lowest was for service outcomes (79.8%), with cost appropriateness rated the lowest (23.9%).Conclusion: The overall patient satisfaction rate with Tam Dao Medical Center was high (89.4%). This result serves as an important foundation for implementing further measures to improve service quality particularly in infrastructure, health communication, and treatment effectiveness with the aim of achieving comprehensive patient satisfaction and providing dedicated care for the community.
Keywords: Patient satisfaction; inpatient treatment; medical center.